A Portrait of Religious Values in an ELT Textbook for Junior High School: A Critical Discourse Analysis - Erina Ismalia Falin (Fakultas Keguruan Dan Ilmu Pendidikan, 2024)
This study analyzes the portrait of religious values in the ELT textbook entitled “Bahasa Inggris Think Globally Act Locally Kelas IX” [English Think Globally Act Locally class IX] used by junior high school students published by the Ministry of Education and Culture of the Republic of Indonesia. The results of the study are divided into two parts of the representation of religious values, namely visual-verbal artifacts presented through a number of images with short conversations and textual artifacts including procedure texts, written advertisements and collections of reading texts with certain topics. Based on the guidelines of the Ministry of Education and Culture on religious values, the research analyzed includes three dimensions of relationships at once: the relationship between individuals and God, the relationship between individuals and other people, and the relationship between individuals and the universe (environment) using Critical Discourse Analysis (CDA) with Fairclough's three-dimensional discourse framework (1995) consisting of description, interpretation and explanation step as a method for analyzing artifacts regarding the relationship of religious values in the textbook. The findings show that three dimensions of religious values have been conveyed in the form of visual-verbal and textual artifacts found in 10 of the 11 chapters in the textbook. Overall, 23 artifacts contained three dimensions of religious values (individual relationship with God, individual relationship with others, and individual relationship with the universe or environment). The dimension of human relationship with God was found the most with 11 artifacts, the dimension of individual with others with 8 artifacts and the dimension of individual with the universe or environment with the least number of artifacts, with only 4 artifacts found.
Reuploud Repository hasyim Mei 2026 Validasi file repositori 26 Mei 2026_(Farrel)_Firli